2012
DOI: 10.1093/nar/gks379
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane helix: simple or complex

Abstract: Transmembrane helical segments (TMs) can be classified into two groups of so-called ‘simple’ and ‘complex’ TMs. Whereas the first group represents mere hydrophobic anchors with an overrepresentation of aliphatic hydrophobic residues that are likely attributed to convergent evolution in many cases, the complex ones embody ancestral information and tend to have structural and functional roles beyond just membrane immersion. Hence, the sequence homology concept is not applicable on simple TMs. In practice, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…Simple and complex helices were determined using TMSOC [7]. The complexity class is determined by calculating the hydrophobicity and sequence entropy.…”
Section: Methodsmentioning
confidence: 99%
“…Simple and complex helices were determined using TMSOC [7]. The complexity class is determined by calculating the hydrophobicity and sequence entropy.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of simple/complex TM regions can be used to distinguish between mere hydrophobic anchors in the membrane (simple TMs) in contrast to complex TMs that fulfil also other structural and/or functional roles 45 - 47 . With the exception of the Plasmodium falciparum case, all other GAA1/GPAA1 sequences studied (human, fly, worm, yeast, Arabidopsis thaliana , Leishmania , Trypanosoma ) have a least 6 complex TMs (as reported by the TMSOC server 45 ). It was experimentally shown that the GAA1/GPAA1 TM regions (especially the C-terminal one with a conserved proline) are important for binding the GPI lipid anchor in a functionally productive manner to the transamidase complex 41 , 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Both proteins B and C have 8 TMS with a 4+4 topology. Only one of the aligned TMSs in the TSUP homolog is classified as simple by TMSOC [30]. Given that we found other lower scoring B-C alignments that involve complex TMSs that fully covered one repeat unit and satisfied all other criteria, we trusted the inference.…”
Section: New Families Added To Togmentioning
confidence: 58%
“…We identified significant alignments between members of the ArsP family and the established TOG families LCT, TSUP, and NiCoT. All aligned TMSs are complex according to the TMSOC program and the classification proposed by Eisenhaber's group [30], decreasing the likelihood of a false positive. Protein OGD29236(B) has 13 TMSs with topology 4+N+4+1 (N = 4), which is apparent from the region that aligns with its homologue in TCDB A8VTI4 (TC: 2.A.119.1.2; Fig 4A) and because the corresponding Pfam domain (PF03773) only covers the first 12 TMSs (Fig 4C).…”
Section: New Families Added To Togmentioning
confidence: 99%
See 1 more Smart Citation